Gibberellin action on growth, development and production of tobacco - Almeida, A. Q. de; Vieira, E. L. (Scientia Agraria Paranaensis, 2000)
This work aimed at evaluating the action of gibberellin on growth, development and production of Nicotiana tabacum L., Type Brasil-Bahia. Liquid gibberellin in doses of 0, 1.25, 3.75, 6.75 and 10.0 mL L-1 was sprayed on leaves of plants grown in greenhouse. The pelleted seeds were sowed in expanded polystyrene trays containing PlantMax®. Fifteen days after sowing (DAS), the treatments were applied. Six sprayings were made once a day, every five days. After 43 DAS, the number of leaves, length of the stem and root, dry matter of stem, leaves and roots, and leaf area were evaluated. In the field, the plants remained for 64 days and the number of total leaves, number of feasible leaves, plant height, dry matter of stem and leaves, and leaf area were evaluated. The results showed that, in the greenhouse, gibberellin increases efficiently the stem length, leaf dry matter and leaf area. In the field, gibberellin does not increase the leaf dry matter and the leaf area of Brasil-Bahia tobacco.